Maternal Age is a Risk Factor for Cesarean Section Following Induction of Labor. Issue 2 (June 2018) - Dunn, L.; Kumar, S.; Beckmann, M.
Abstract : ( Aust N Z J Obstet Gynaecol . 2017;57(4):426–431) Women 35 years or older, considered advanced maternal age (AMA), are more likely to experience complications and adverse neonatal outcomes including stillbirth. Pregnancies in these older women are increasing in western countries. Scheduled induction of labor in AMA pregnancies has been increasingly practiced; however, data concerning the outcomes of induction of labor (IOL) in AMA pregnancies are limited. This study explored the relationship between IOL and cesarean delivery in AMA women.